Membangun Brand Image dan Brand Awareness Produk UMKM Depok Melalui Bazar - Fatimah, Fatimah; Aminah, Indianik; Puspa Alyssa, Heidy; Ingriyani, Lini (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Micro, Small and Medium Enterprises (MSMEs) of Iwapi Depok City members are partially able to market their products online by selling products in the marketplace. It's just that online marketing does not directly make the market for MSME products wider. MSMEs must build brand image and brand awareness by creating a unique product identity, attractive slogans, colors, logos and brands that can represent the product. Building a strong brand image and brand awareness with limited resources is challenging. One solution is to conduct direct marketing communication through bazaar activities. Communication skills are needed to support this activity. Therefore, it is necessary to conduct training to improve interpersonal business communication skills for MSME actors participating in the bazaar. This training targets MSME actors who are members of Iwapi Depok who have the goal of improving marketing communication skills in business. The training method refers to the theory of PAR or Participatory Action Research and the benchmark used to assess the success of this empowerment program with the KUPAR cycle. Evaluation of the effectiveness level of training activities using the pre-test average score and post-test average score.The training activity succeeded in improving the knowledge and business communication skills of the participants with a significance number (α) < 0.05. This means that Ho was rejected, there was a significant difference between the average pre-test score and the post-test average score. Business communication skills are implemented in bazaar activities. The bazaar which was held in the yard of Depok City Hall could be carried out well. The success of bazaar activities is evidenced by an increase in sales turnover and a 60% increase in profits during bazaar activities and a 20% increase in profits after the completion of bazaar activities.